2017
DOI: 10.5455/njppp.2017.7.1040508112017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of two selected resistance training patterns on some physical and physiological factors of elite freestyle wrestler young boys

Abstract: Background: Wrestling is a sport heavy and severe activity due to certain physical and physiological needs such as anaerobic, power, strength, speed, lactate tolerance, and anaerobic stamina because wrestling matches are carried out at different weights. A more successful wrestling is a more effective athletic performance for repeated exercises and endurance fatigue. Aims and Objectives: The main objective of this research was to compare the effect of two resistance training methods (dual pyramid and diagonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In short, the pyramidal method is an effective method for training for strength, hypertrophy, and power while having the added benefit of enhancing muscular endurance. This suggests that the pyramidal method is a good candidate for athletes who practice wrestling because combat training involves aerobic training interspersed with anaerobic effort [11]. Although the use of resistance in addition to endurance training is an interesting topic, the practice of resistance training should be carefully considered in light of the type of endurance performed, the training experience of the athlete (an improvement in the lactic threshold was only observed for beginners), the intensity of the endurance session (lower than 75 to 85% of VO 2 max), and its potential on the maximal aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In short, the pyramidal method is an effective method for training for strength, hypertrophy, and power while having the added benefit of enhancing muscular endurance. This suggests that the pyramidal method is a good candidate for athletes who practice wrestling because combat training involves aerobic training interspersed with anaerobic effort [11]. Although the use of resistance in addition to endurance training is an interesting topic, the practice of resistance training should be carefully considered in light of the type of endurance performed, the training experience of the athlete (an improvement in the lactic threshold was only observed for beginners), the intensity of the endurance session (lower than 75 to 85% of VO 2 max), and its potential on the maximal aerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Mohammadi et al [11], research outputs on triangle pyramids are conflicting. Previous studies have suggested that two different triangle pyramidal exercises lead to similar strength, endurance, hypertrophy, and anaerobic power outcomes, and also that different pyramidal patterns produce different outcomes based on which body limb is trained.…”
Section: Comparison Of Triangle Methodsmentioning
confidence: 99%
See 3 more Smart Citations